2008
DOI: 10.1007/s00380-007-1009-6
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the azygos arch valves on multidetector-row computed tomography

Abstract: To evaluate the frequency and appearance of the azygos arch valves on chest examinations using multidetector-row computed tomography (MDCT), we retrospectively reviewed findings from 194 contrast-enhanced MDCT examinations of the chest. Rate of injection of 300 mgI/ml contrast materials was low (2.0 ml/s) and high (3.0 ml/s). Scanning delay was 80 s on examination on low-rate injection of contrast material and 20 s on high-rate injection of contrast material. The presence of residual contrast material in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…Past reports have revealed that reflux of contrast material into the azygos arch is commonly seen in CT images, especially when the injection rate was high [3,4]. The findings of the present study indicate that the reason for this is that the contrast material clashes with the efferent blood flow in the SVC during the diastolic phase and refluxes into the azygos vein.…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations
“…Past reports have revealed that reflux of contrast material into the azygos arch is commonly seen in CT images, especially when the injection rate was high [3,4]. The findings of the present study indicate that the reason for this is that the contrast material clashes with the efferent blood flow in the SVC during the diastolic phase and refluxes into the azygos vein.…”
Section: Discussioncontrasting
confidence: 40%
“…The findings of the present study indicate that the reason for this is that the contrast material clashes with the efferent blood flow in the SVC during the diastolic phase and refluxes into the azygos vein. If the injection rate is high, the degree of reflux becomes more pronounced as indicated in previous reports [3,4]. Then, the reflux of contrast material will generally be dammed by the azygos arch valves.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Similar valves have been also found in the terminal segments of vertebral veins (Scapinelli, 2000) and in the azygous arch (Yeh et al, 2004;Ichikawa et al, 2008). These proximally situated valves may play a role in avoiding or limiting the venous refluxes.…”
Section: Intracranial Pathological Venous Hemodynamics In the Multiplmentioning
confidence: 84%